1998
DOI: 10.1074/jbc.273.37.24249
|View full text |Cite
|
Sign up to set email alerts
|

A p56 -independent Pathway of CD2 Signaling Involves Jun Kinase

Abstract: The p56lck Src family non-receptor tyrosine kinase has been shown to be critical for T lymphocyte differentiation and activation. Hence in the absence of p56 lck , T cell receptor triggered activation does not occur. We now provide evidence for a CD2-based signaling pathway which, in contrast to that of the T cell receptor, is independent of p56 lck . CD2-mediated interleukin-2 production occurs via activation of Jun kinase in cell lines lacking p56 lck . Jun kinase then facilitates the binding of c-Jun/c-Fos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 89 publications
4
17
0
Order By: Relevance
“…ZAP-70 is essential for Ca 2ϩ influx, persistent phosphorylation of , cytokine production, and proliferation. This is consistent with earlier observations showing that CD2-mediated activation of T cells requires expression of the -chain (14,15) and induces phosphorylation (8) and ZAP-70 tyrosine phosphorylation in Jurkat T cells, although to a lesser extent than activation through the TCR (13). Our finding that ZAP-70 is essential for CD2-mediated persistent phosphorylation of in human mature T cells is consistent with a previous report showing that CD3 activation does not induce phosphorylation in another ZAP-70-deficient model, the P116 Jurkat T cell clone (31).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…ZAP-70 is essential for Ca 2ϩ influx, persistent phosphorylation of , cytokine production, and proliferation. This is consistent with earlier observations showing that CD2-mediated activation of T cells requires expression of the -chain (14,15) and induces phosphorylation (8) and ZAP-70 tyrosine phosphorylation in Jurkat T cells, although to a lesser extent than activation through the TCR (13). Our finding that ZAP-70 is essential for CD2-mediated persistent phosphorylation of in human mature T cells is consistent with a previous report showing that CD3 activation does not induce phosphorylation in another ZAP-70-deficient model, the P116 Jurkat T cell clone (31).…”
Section: Discussionsupporting
confidence: 81%
“…It has been demonstrated that CD2-mediated signaling can occur independently of the ITAMs of the -chain (18). CD2 activation of the JCAM1.6 clone of Jurkat leukemia cells, which lacks Lck expression, can activate the c-Jun N-terminal kinase involved in IL-2 regulation of transcription (13). CD3-mediated activation of these cells induces neither c-Jun N-terminal kinase activation nor IL-2 transcription (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine 402 of Pyk2 is critical for its function, probably through formation of a Pyk2-Fyn complex leading to the activation of Rac1-JNK pathway followed by the production of IL-2. Recent findings suggest that Pyk2 may function downstream of LFA-1 (39) and of CD2 (40). As LFA-1 and CD2 are critical for the formation of immunological synapse (41), Pyk2 might function in forming or sustaining it for full activation of the T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike TCR␣␤, the pre-TCR has an additionally extended cytoplasmic tail encoded by the pT␣ gene. Within the tail two proline-rich motifs can be identified by sequence similarity to motifs in the cytoplasmic tail of human CD2 that mediate binding to CD2BP2, an adaptor molecule involved in intracellular signaling (8,16). Heretofore, the importance of the intracytoplasmic region of the pre-TCR has been uncertain, but very recently the expression of pT␣ mutants in retrovirally transduced T cell precursors and cell lines showed that the pT␣ cytoplasmic tail, in particular the proline-rich domain, plays a crucial role in pre-TCR signal transduction (17).…”
mentioning
confidence: 99%